Semisynthesis of Ingenol 3-Angelate (PEP005): Efficient Stereoconservative Angeloylation of Alcohols - Liang, Xifu; Grue-Sørensen, Gunnar; Petersen, Anders Klarskov; Högberg, Thomas (Synlett, 2012)
A high-yielding method was developed for the preparation of ingenol 3-angelate (PEP005, ingenol mebutate) via the corresponding 5,20-acetonide without concomitant isomerization of the angelate (Z-form) to the corresponding tiglate (E-form). The general scope of the stereoconservative esterification method was further evaluated on several different alcohols, giving the angelates in up to quantitative yield without isomerization to the tiglate.
Keywords: ingenol; ingenol 3-angelate; PEP005; angeloylation; isomerization; tiglate